Influence of Varying Synthetic Routes on the Physicochemical Properties of Mg-Al-CO3 and Zn-Al-CO3 Hydrotalcite-Like Compounds: A Comparative Study - Omonmhenle, Selina Ilunakan; Shannon, Ian James (European Scientific Journal, ESJ, 2019)
Magnesium-Aluminium Carbonate Hydrotalcite-like Compound (Mg-Al-CO3-HTlc) and Zinc-Aluminium Carbonate Hydrotalcite-like Compound (Zn-Al-CO3-HTlc) with Mg/Al and Zn/Al atomic ratio 2:1 was synthesized by co-precipitation and urea hydrolysis methods. Their physicochemical properties were studied using powder X-ray diffraction (PXRD), X-ray fluorescence spectrophotometry (XRF), Fourier transform infrared (FTIR) and Thermogravimetry (TG) and Differential Thermal Analysis (DTA) involving evolved gas analysis (EGA). The PXRD of the synthesized material showed that the crystallinity is influenced by the type of synthetic method and can affect the properties of the hydrotalcite-like compounds. The TG, DTA and EGA results showed that three steps of mass loss occurred corresponding to the release of gallery water, structural water and carbon dioxide (from carbonate decomposition) respectively. Thermal treatment up to about 500oC and beyond transforms them into nonstoichiometric metal stable oxides (MgO and ZnO) whose crystallinity is lower than that of the precursor and then into stable spinel with no further mass loss following the transformation. Derivatives of urea hydrolysis method gave better ordered and more crystalline Mg2AlCO3-HTlc but with smaller unit cell. Variation in synthesis route can influence the mode of stacking of the layers, order of the interlayer anions and water molecules in the gallery space and attraction between the interlayer anions and the hydroxyl ions of the metal hydroxide layers.